Friedrich Nietzsche, On the Genealogy of Morals and Criminology - Ranasinghe, Prashan (Theoretical criminology, 2022)
The writings of Friedrich Nietzsche have much to offer criminology. To date, however, his work has been largely neglected in this scholarship. Taking this lacuna seriously, this article reads Nietzsche’s second essay of On the Genealogy of Morals and explicates its importance to criminology. Specifically, focus is cast upon Nietzsche’s exposition of crime and particularly punishment, pertaining to the production of a calculating and calculable being upon whom pain and suffering can be inflicted and the ways that concerns over excesses of punishment come to be framed as problematic. Via this reading, it is claimed that On the Genealogy of Morals can serve, among others, as an important critique to many of the presuppositions that ground the classical school of criminology, epitomized in the work of Cesare Beccaria and Jeremy Bentham. The article concludes by locating the importance of Nietzsche to penology specifically and criminology more broadly.